A Novel Conductive Core–Shell Particle Based on Liquid Metal for Fabricating Real‐Time Self‐Repairing Flexible Circuits. (19th February 2020) - Zheng, Rongmin; Peng, Zefei; Fu, Ying; Deng, Zhifu; Liu, Shuqi; Xing, Shuting; Wu, Yaoyi; Li, Junyun; Liu, Lan
Abstract: As a critical part of flexible electronics, flexible circuits inevitably work in a dynamic state, which causes electrical deterioration of brittle conductive materials (i.e., Cu, Ag, ITO). Recently, gallium‐based liquid metal particles (LMPs) with electrical stability and self‐repairing have been studied to replace brittle materials owing to their low modulus and excellent conductivity. However, LMP‐coated Ga2 O3 needs to activate by external sintering, which makes it more complicated to fabricate and gives it a larger short‐circuit risk. Core–shell structural particles (Ag@LMPs) that exhibit excellent initial conductivity(8.0 Ω sq −1 ) without extra sintering are successfully prepared by coating nanosilver on the surface of LMPs through in situ chemical reduction. The critical stress at which rigid Ag shells rupture can be controlled by adjusting the Ag shell thickness so that LM cores with low moduli can release, achieving real‐time self‐repairing (within 200 ms) under external destruction. Furthermore, a flexible circuit utilizing Ag@LMPs is fabricated by screen printing, and exhibits outstanding stability and durability (R/R0 < 1.65 after 10 000 bending cycles in a radius of 0.5 mm) because of the functional core–shell structure. The self‐repairable Ag@LMPs prepared in this study are a candidate filler for flexible circuit design through multiple processing methods. Abstract : A novel core–shell conductive particle based on liquid metal (Ag@LMPs) is developed. This particle exhibits excellent conductivity without external sintering, while simultaneously exhibiting long‐term durability and real‐time self‐repairing in flexible circuits owing to the release of the liquid metal core. These Ag@LMPs are a candidate filler for self‐repairing flexible circuit design.